Evaluation of flurazepam and placebo on sleep disorders in childhood - Rubens Reimão; Antonio B. Lefévre (Arquivos de Neuro-Psiquiatria)
The clinically observed results in 40 patients, from 1 to 15 years old, presenting sleep disturbances, in a comparative and statistically approached study of flurazepam 15mg daily against placebo, are reported. Placebo was administered, followed by the drug, during 14 days each. The chief complaints were sleepwalking, sleep-talking, sleep terror, sleep-related bruxism, sleep-related headbanging, insomnia and excessive movements during sleep. A significant effect of flurazepam on sleepwalking, sleep-talking, bruxism, sleep terror and excessive movement during sleep, was observed. The insomniac and headbanging patients were not enough for statistical analysis. Flurazepam side effects were excessive drowsiness during daytime in 3 cases; irritability, 3 cases; nausea and vomiting, 2 cases, and were not correlated with age. Placebo side effects were similar, except for nausea and vomiting which were not observed. It was necessary to discontinue flurazepam in 2 cases, because of excessive drowsiness during daytime, which did not improve when reducing the dose.